New developments and application in chemical reaction engineering : proceedings of the 4th Asia-Pacific Chemical Reaction Engineering Symposium (APCRE '05), Gyeongju, Korea, June 12-15, 2005 - Rhee, Hyun-Ku, 1939-; Nam, In-Sik, 1950-; Park, Jong Moon (Studies in surface science and catalysis, 2006)
This Proceedings of APCRE'05 contains the articles that were presented at the 4th Asia-Pacific Chemical Reaction Engineering Symposium (APCRE05), held at Gyeongju, Korea between June 12 and June 15, 2005, with a theme of "New Opportunities of Chemical Reaction Engineering in Asia-Pacific Region". Following the tradition of APCRE Symposia and ISCRE, the scientific program encompassed a wide spectrum of topics, including not only the traditional areas but also the emerging fields of chemical reaction engineering into which the chemical reaction engineers have successfully spearheaded and made significant contributions in recent years. In addition to the 190 papers being accepted, six plenary lectures and 11 invited lectures are placed in two separate chapters in the front. * Provides an overview of new developments and application in chemical reaction engineering * Topics include traditional and emerging fields * Papers reviewed by experts in the field